Competent Teacher Ideal Professional Certified Character and Progressive Perspective of Kitab Al-Rasul Al-Muallim - Muthoifin; Alberto Emmanuel Conti Morales; Mr. Anat Maisu; Ika Safitri Windiarti; Eltom Ishaq Osman Musa (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study is to evaluate the notion of teacher competency in Islamic education as it is presented in the book al-Rasulul al-Mu'allim. This study included library research from a variety of books or scriptures related to competency, teachers, Islamic education, Sheikh Abdul Fattah's biography, the Prophet Muhammad's teaching style, literature on teaching, and Sheikh Abdul Fattah's ideas. The book Al Rasul Al Mu'allim was the main source of inquiry and study for the data. Content analysis, normative, and theological methodologies are utilized to investigate the topic of divinity and the characters of God, as well as the teachings of Allah's religion. Religious pedagogical competence, religious personality competence, religious professional competence, religious social competence, religious global competence, and religious emotional competence were identified as six teacher competencies in Islamic education. The results of the study on the Performance of Good Educators in the Book of Al-Rasul al-Muallim can be implemented by anyone, in any institution, and at any time, because it is very relevant to the vision, mission, and real educational goals.